2023
DOI: 10.4271/2023-24-0033
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Effect of Injector Nozzle Hole Number on Diesel Engine Performance under Plateau Conditions

Junliang Zhao,
Ruomiao Yang,
Yuchao Yan
et al.

Abstract: <div class="section abstract"><div class="htmlview paragraph">Diesel engines operated at high altitudes would experience performance degradation due to the fuel-air amount mismatch, resulting in combustion deterioration. Technologies that supplement oxygen concentration, such as intake oxygen enrichment, turbocharging and the addition of oxygenated fuel additives, can help restore performance at high altitudes, but each has its own limitations Operating diesel engines at high altitudes still genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Other authors draw attention to the dependence of nitrogen oxide emissions on altitude. The team of authors [40][41][42] examined the emission of nitrogen oxides from diesel engines and found a significant depletion of the fuel-air mixture at high altitudes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other authors draw attention to the dependence of nitrogen oxide emissions on altitude. The team of authors [40][41][42] examined the emission of nitrogen oxides from diesel engines and found a significant depletion of the fuel-air mixture at high altitudes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As mentioned previously, this procedure often requires multiple tests, both in the laboratory and on the road, which in turn involves increased financial costs and time commitments. Therefore, it becomes increasingly necessary to develop an alternative test method that would provide a better representation of real driving conditions and would enable the individualization of the test, e.g., depending on the type of vehicle or type of drive [10][11][12]. The authors of [13] also attempted to correlate the WLTC test with the RDE, in which they defined the basic steps for conducting the RDE test cycle under laboratory conditions.…”
Section: Parameter Euro 6dmentioning
confidence: 99%
“…The study will incur to be costly and timeconsuming. Therefore, CFD simulation has become a valuable tool for investigating and developing control strategies for the engine due to its higher flexibility and lower cost compared to the experimental approach [29]. The latest Computer Fluid Dynamic (CFD) software employs a highly efficient coupling of detailed chemical kinetics, liquid fuel spray and turbulent gas dynamics in order to simulate combustion processes occurring in an internal combustion engine.…”
Section: Introductionmentioning
confidence: 99%